Revisiting Metal Dihalide Complexes with Phosphine Ligands: Isostructurality, Steric Effects, Anagostic Interactions, Crystal Voids, and Energetic Calculations - Pérez Pérez, Hiram (2024)
The crystal structures of seven metal dihalide complexes with triphenylphosphine (PPh₃) and two with tribenzylphosphine (PBz₃) have been reanalyzed. The studied complexes include [FeCl₂(PPh₃)₂], [CoCl₂(PPh₃)₂], [CoBr₂(PPh₃)₂], [NiCl₂(PPh₃)₂], [NiBr₂(PPh₃)₂], [NiI₂(PPh₃)₂], [ZnCl₂(PPh₃)₂], [NiCl₂(PBz₃)₂], and [NiBr₂(PBz₃)₂]. A detailed geometric analysis revealed high isostructurality among several pairs. Ligand steric effects were assessed using cone angles and percentage surface coverage. Crystal packing is stabilized by weak C─H⋯π and C─H⋯X (X = Cl, Br, and I) interactions. Notably, [NiCl₂(PBz₃)₂] and [NiBr₂(PBz₃)₂] feature rare intramolecular C─H⋯Ni anagostic interactions. Reduced density gradient (RDG) and noncovalent interaction (NCI) plots confirmed weakly attractive C─H⋯π contacts in all complexes. Void-volume analysis assessed the mechanical strength of the crystals, while pixel energy and energy frameworks clarified structural stability and dominant interactions. Density Functional Theory (DFT) calculations, along with QTAIM/NCIplot and NBO analyses, as well as electron density (ED) versus electrostatic potential (ESP) plots, were performed to better understand the C─H···Ni interactions and distinguish between agostic and anagostic interactions.